Peran Orang Tua dan Tenaga Kesehatan terhadap Kejadian Kehamilan Usia Remaja dan Kehamilan Usia Produktif di Puskesmas Wairiang Kabupaten Lembata, NTT - Masan, Herlinda Perada; Amalia, Rize Budi; Kharimah, Azimatul; Prasetyo, Budi (Universitas Batanghari Jambi, 2024)
Teenage pregnancies in Indonesia are increasing every year, including in Lembata Regency, NTT. Teenage pregnancy has a negative impact on physical growth, development of thinking, language, emotions and socio-economics so immediate treatment is needed. This study aims to analyze the role of health workers and the role of parents in the incidence of teenage pregnancies and productive age pregnancies at the Wairiang Community Health Center, Lembata Regency, NTT. Type of observational analytical research with a case control approach. The sampling technique used the consecutive sampling method with a sample size of 64 primigravida pregnant women at the Wairiang Health Center. By dividing the case group (adolescent primigravida) into 16 people and the control group (productive age primigravida) into 48 people. The research instrument used was a questionnaire. Data analysis using Chi square test. The results of the study show that the factor that has a significant relationship with first pregnancy as a teenager is the role of parents, while the role of health workers does not have a significant relationship with teenage pregnancy.